RNA mimicry by the fap7 adenylate kinase in ribosome biogenesis. - Jérôme Loc'h (Public Library of Science (PLoS), 2014)
During biogenesis of the 40S and 60S ribosomal subunits, the pre-40S particles are exported to the cytoplasm prior to final cleavage of the 20S pre-rRNA to mature 18S rRNA. Amongst the factors involved in this maturation step, Fap7 is unusual, as it both interacts with ribosomal protein Rps14 and harbors adenylate kinase activity, a function not usually associated with ribonucleoprotein assembly. Human hFap7 also regulates Cajal body assembly and cell cycle progression via the p53-MDM2 pathway. This work presents the functional and structural characterization of the Fap7-Rps14 complex. We report that Fap7 association blocks the RNA binding surface of Rps14 and, conversely, Rps14 binding inhibits adenylate kinase activity of Fap7. In addition, the affinity of Fap7 for Rps14 is higher with bound ADP, whereas ATP hydrolysis dissociates the complex. These results suggest that Fap7 chaperones Rps14 assembly into pre-40S particles via RNA mimicry in an ATP-dependent manner. Incorporation of Rps14 by Fap7 leads to a structural rearrangement of the platform domain necessary for the pre-rRNA to acquire a cleavage competent conformation.